High-fat diet-induced deregulation of hippocampal insulin signaling and mitochondrial homeostasis deficiences contribute to Alzheimer disease pathology in rodents - Petrov, Dmitry; Pedrós, Ignacio; Artiach, Gonzalo; Sureda, Francesc X.; Barroso, Emma; Pallàs, Mercè; Casadesús, Gemma; Beas-Zarate, Carlos; Carro, Eva; Ferrer, Isidro; Vazquez-Carrera, Manuel; Folch, Jaume; et al. (Biochimica et biophysica acta, 2015)
Global obesity is a pandemic status, estimated to affect over 2 billion people, that has resulted in an enormous strain on healthcare systems worldwide. The situation is compounded by the fact that apart from the direct costs associated with overweight pathology, obesity presents itself with a number of comorbidities, including an increased risk for the development of neurodegenerative disorders. Alzheimer disease (AD), the main cause of senile dementia, is no exception. Spectacular failure of the pharmaceutical industry to come up with effective AD treatment strategies is forcing the broader scientific community to rethink the underlying molecular mechanisms leading to cognitive decline. To this end, the emphasis is once again placed on the experimental animal models of the disease. In the current study, we have focused on the effects of a high-fat diet (HFD) on hippocampal-dependent memory in C57/Bl6 Wild-type (WT) and APPswe/PS1dE9 (APP/PS1) mice, a well-established mouse model of familial AD. Our results indicate that the continuous HFD administration starting at the time of weaning is sufficient to produce β-amyloid-independent, hippocampal-dependent memory deficits measured by a 2-object novel-object recognition test (NOR) in mice as early as 6months of age. Furthermore, the resulting metabolic syndrome appears to have direct effects on brain insulin regulation and mitochondrial function. We have observed pathological changes related to both the proximal and distal insulin signaling pathway in the brains of HFD-fed WT and APP/PS1 mice. These changes are accompanied by a significantly reduced OXPHOS metabolism, suggesting that mitochondria play an important role in hippocampus-dependent memory formation and retention in both the HFD-treated and AD-like rodents at a relatively young age. [Display omitted] •We have detected a significant decrease in insulin signaling in the hippocampus.•We have detected an upregulation of both CDK5 and GSK-3β kinases in the hippocampus.•We detected significant decreases in mitochondrial OXPHOS complex proteins.•The mitochondrial dysfunction is a key culprit leading to cognitive decline.